An economic analysis of a system wide Lean approach: cost estimations for the implementation of Lean in the Saskatchewan healthcare system for 2012–2014 - Sari, Nazmi (BMC Health Serv Res, 2017)
BACKGROUND: The costs of investing in health care reform initiatives to improve quality and safety have been underreported and are often underestimated. This paper reports direct and indirect cost estimates for the initial phase of the province-wide implementation of Lean activities in Saskatchewan, Canada. METHODS: In order to obtain detailed information about each type of Lean event, as well as the total number of corresponding Lean events, we used the Provincial Kaizen Promotion Office (PKPO) Kaizen database. While the indirect cost of Lean implementation has been estimated using the corresponding wage rate for the event participants, the direct cost has been estimated using the fees paid to the consultant and other relevant expenses. RESULTS: The total cost for implementation of Lean over two years (2012–2014), including consultants and new hires, ranged from $44 million CAD to $49.6 million CAD, depending upon the assumptions used. Consultant costs accounted for close to 50% of the total. The estimated cost of Lean events alone ranged from $16 million CAD to $19.5 million CAD, with Rapid Process Improvement Workshops requiring the highest input of resources. CONCLUSIONS: Recognizing the substantial financial and human investments required to undertake reforms designed to improve quality and contain cost, policy makers must carefully consider whether and how these efforts result in the desired transformations. Evaluation of the outcomes of these investments must be part of the accountability framework, even prior to implementation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-017-2477-8) contains supplementary material, which is available to authorized users.